Urodynamic parameters as predictors of percutaneous tibial nerve stimulation outcomes in overactive bladder patients - Indraswari, Madhyra Tri; Rahardjo, Harrina Erlianti; Seno, Doddy Widyawan Hami; Mirza, Hendy; Afriansyah, Andika (Faculty of Medicine Universitas Indonesia, 2025)
BACKGROUND Percutaneous tibial nerve stimulation (PTNS) is an emerging overactive bladder (OAB) treatment. However, some patient characteristics can affect its effectiveness. Urodynamic studies help diagnose OAB by evaluating bladder function. This study aimed to identify prognostic factors for PTNS treatment based on urodynamic parameters. METHODS A retrospective study was performed on 108 patients with OAB who underwent PTNS at Persahabatan Hospital, Jakarta, Indonesia, between January 2022 and January 2023. Patients with primary OAB received an 8-week PTNS regimen and were grouped into success and failure. Pre-treatment urodynamic parameters were extracted and compared between groups. Additional multivariate Cox regression analysis was performed to identify risk factors associated with PTNS failure. RESULTS Of 108 patients (mean age: 51.69 [17.5]), 77 (73.1%) responded favorably to PTNS treatment. Three significant covariates of PTNS failure were identified: initial sensation volume (hazard ratio [HR]: 6.312; 95% confidence interval [CI]: 1.94−20.49), detrusor overactivity (DO) (HR: 8.476; 95% CI: 1.89−38.095), and infravesical obstruction (IVO) (HR: 5.213; 95% CI: 1.40−19.41). CONCLUSIONS Urodynamic predictors including abnormal first sensation volume, DO, and IVO were observed as risk factors for PTNS failure. These findings can help medical professionals personalize PTNS treatment, enhancing patient outcomes and satisfaction.